Efektivitas Program Pembinaan Kedisiplinan Dalam Proses Belajar Mengajar Terhadap Etos Kerja Mandiri Guru - Rodince Siahaan (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The purpose of this study was to determine the relationship between teaching discipline in the classroom and improving the quality of self-competence for teachers. The research location is SD Negeri 030435 Pardomuan, Kingdom sub-district, involving six teachers. The results showed that in the first cycle, the observation results were